Context dependent and independent mechanisms of time perception in the human brain - Wiener, Martin (ProQuest Dissertations & Theses, 2012)
The perception of time is one of the hallmarks of conscious experience. However, despite this importance, time is a relatively understudied dimension in psychology and cognitive neuroscience. A central question within the time perception literature is whether timing relies on a unitary, context independent neural mechanism, or whether timing is a distributed process that relies on multiple, context dependent circuits. A series of experiments drawing on a variety of methodologies were conducted in order to address this question. First, a series of meta-analyses, each modeling neuroimaging results on time perception studies, were conducted utilizing the Activation Likelihood Estimation (ALE) algorithm. Studies were divided on the bases of task variation, interval length, and explicit or implicit engagement of temporal processing. The results revealed dissociable, yet partially overlapping, neural networks that are selectively engaged for timing under different temporal contexts. Second, meta-analytic results were used to guide stimulation of a site within the right supramarginal gyrus (SMG), a site implicated during the processing of sub-second intervals, with Transcranial Magnetic Stimulation (TMS). Across a series of experiments, right SMG stimulation was found to selectively increase the length of perceived duration of a visual stimulus. An additional study utilized simultaneous TMS and Electroencephalography to demonstrate that SMG stimulation led to an increase in amplitude of a slow-wave negative cortical potential over frontocentral sites that correlated between subjects, such that individuals with larger increases in amplitude experienced a longer subjective duration than those with small or no change. Third, results from the meta-analysis also suggested dissociations between nigrostriatal and mesocortical dopamine pathways in the timing of sub-second and supra-second intervals, respectively. A behavioral genetics demonstrated that subjects with polymorphisms separately affecting different dopamine circuits were selectively impaired on a time perception task at distinct duration ranges, suggesting differential engagement of the dopamine system across different temporal contexts. These results suggest that timing is mediated by independent, but partially overlapping neural systems, which may be flexibly engaged depending on the task requirements, such that single or multiple systems may be active during any one timing task, depending on environmental conditions and behavioral requirements.